Socio-Economic Development of Russia at the Contemporary Stage; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Korshunova L. A. Lydia; Kuzmina N. G. Nataliya Gennadjevna; Litovchenko A. I. Anna; Babayeva F. G. Fidan (2017, 2017)
Title screen